2019
DOI: 10.1002/bsd2.80
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility reporting and corporate governance mechanisms: An international outlook from emerging countries

Abstract: Within corporate governance, the board of directors plays a major role in improving corporate transparency by increasing the disclosure of corporate social responsibility (CSR) information. In this paper, we analyse the effect of board composition, particularly board independence, board gender diversity, CEO duality, and the presence of a CSR board committee on CSR reporting. Evidence of this effect is still scarce when it concerns the effect of corporate governance mechanisms and CSR disclosure in firms perta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 112 publications
(198 reference statements)
6
48
0
Order By: Relevance
“…Similarly, Joyce and Paquin (2016) conclude that sustainability practices contribute to environmental, social, governance, and economic value creation, despite being assessed differently by diverse cultures. Gallego‐Álvarez and Pucheta‐Martínez (2020) obtain the same conclusion for sustainability reporting. Our results support these conclusions for the different types of SPI.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Joyce and Paquin (2016) conclude that sustainability practices contribute to environmental, social, governance, and economic value creation, despite being assessed differently by diverse cultures. Gallego‐Álvarez and Pucheta‐Martínez (2020) obtain the same conclusion for sustainability reporting. Our results support these conclusions for the different types of SPI.…”
Section: Discussionsupporting
confidence: 54%
“…With the growing importance of CSR, recent studies proposed that independent directors may also align the interests of firms with those of stakeholders (Gallego-Álvarez & Pucheta-Martínez, 2020), and tested this proposition by incorporating board independence in CSR studies. However, the findings are inconclusive; some studies found that board independence improves CSR engagement (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020), others found that it decreases (Adel, Hussain, Mohamed, & Basuony, 2019), and still others found a neutral effect (Michelon & Parbonetti, 2012). Therefore, our study provides additional evidence of the influence of independent directors on CSRP.…”
Section: Findings and Discussionmentioning
confidence: 56%
“…the authors attribute this situation to the immaturity or small proportion of CSR committees in the sampled firms (Michelon & Parbonetti, 2012). Past evidence also indicated that CSR committees are influential in fostering CSR practices of firms in emerging countries (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020). As sectoral evidence, Uyar et al (2020) proved that logistics firms with CSR committees are more likely to publish a higher number of CSR reports over the years.…”
Section: Findings and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reform initiatives such as appointing more IDs onto boards are expected to uncover corporate deception (Bhagat, Brickley, & Coles, 1987). Since enhanced board independence instils an independent and competent view of the board (Gallego‐Álvarez & Pucheta‐Martínez, 2020), it may work as a catalyst to minimise window dressing of statements. Beasley's (1996) study in a developed country context shows that more corporate fraud takes place in firms where insider directors are appointed, and the extent of fraud lessens significantly with the appointment of IDs.…”
Section: Literature Reviewmentioning
confidence: 99%